Proceedings 19th IEEE VLSI Test Symposium. VTS 2001
DOI: 10.1109/vts.2001.923434
|View full text |Cite
|
Sign up to set email alerts
|

Novel spectral methods for built-in self-test in a system-on-a-chip environment

Abstract: pseudo-random test pattern generators in BIST schemes.This new method of built-in self-test (BIST) for sequential cores on a system-on-a-chap (SOC) generates test patterns using a real-time program that runs on an embedded processor. Alternatively, the same program can be run on an external low-cost tester. This program generates patterns using circuit-specific spectral information in the f o r m of one or more Hadamard coefficients. The coefficients are extracted from high fault-coverage compacted pattern se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The generated vectors are the same as or are very close to those generated by actual hardware and include quantization errors, which would not be included in a purely software based method [7], thus giving more pragmatic results. We implemented BIST on eight ISCAS'89 benchmark circuits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generated vectors are the same as or are very close to those generated by actual hardware and include quantization errors, which would not be included in a purely software based method [7], thus giving more pragmatic results. We implemented BIST on eight ISCAS'89 benchmark circuits.…”
Section: Resultsmentioning
confidence: 99%
“…Giani et al [7] proposed a BIST scheme that replicates beneficial spectral components using an in-built microprocessor. Chen and Hsiao [4] applied that method only to hard to detect faults.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsiao and Seth [23] further expanded that work to compact testing. More recently, Giani et al [17,18] have reported spectral techniques for sequential ATPG and built-in self-test. Hsiao's group at Virginia Tech has published further work on spectrum-based self test and core test [7,8,28].…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao and Seth [12] further expanded that work to compact testing. More recently, Giani et al [9,10] have reported spectral techniques for sequential ATPG and built-in self-test. Hsiao's group at Virginia Tech has published further work on spectrum-based self test and core test [2,3,16].…”
Section: Introductionmentioning
confidence: 99%